Botanical Trap Limbah Daun Cengkeh (Syzygium aromaticum) sebagai Pengendalian Lalat Buah (Bactrocera spp.) pada Tanaman Cabai (Capsicum spp.) - Septya Ayu Dwintha; Husaini Purnama Aji; Irfan Mohandis Haraki; Messa Syahputri; Miftah Ajengtiyas Nursyahidah Rahman; Vira Puspitasari (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Dwintha SA, Aji HP, Haraki IM, Syahputri M, Rahman MAN, Puspitasari V. 2021. Botanical traps of clove leaf waste (Syzygium aromaticum) to control of fruitflies (Bactrocera spp.) on chili (Capsicum spp.). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 320-328. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The attack of fruitflies (Bactrocera spp.) on red chili plants is one of the most important problem in the red chili production process. Usually, farmers prefer the synthetic pesticides in controlling fruitflies. However, this method has a negative impact, such as resistance and resurgence of the target pest. This review aimed to provide information about the benefits of clove leaf residue's compounds as an innovation by the combined bioattractants through the application of botanical traps in controlling fruitflies. This writing method used an analyzed literature which developed into an understandable review. Clove leaf residue's extraction contained about 70-96 % methyl eugenol. Clove leaf residue's bioattractants could release volatile compounds containing methyl eugenol that was able to attract male fruitflies. The botanical traps system had the ability to attract fruitflies and could be used for a long time. The application of botanical traps caused disruption of sexual communication so that mating disorders occured in fruitflies. The conclusion is that methyl eugenol compound in clove leaf residue could be used as a bioattractant to replace synthetic attractants which combined with botanical traps.